Online Learning Models in The Era and Post-Pandemic COVID-19 - Asyrul Fikri; Firdaus LN; Hadriana Hadriana; Sumarno Sumarno (STKIP Singkawang, 2023)
Pandemic COVID-19 has shifted education from face-to-face teaching to online-based distance learning. Educators must prepare strategic steps in responding to this transition to achieve learning objectives. To implement an online learning system, learning strategies and models that meet online learning demands must be made. For this reason, this study aims to analyze the online learning model in the era and post-pandemic COVID-19. Literature research methods are used in this study. Data sources were obtained by collecting relevant literature such as books, journals or scientific articles related to the topic: (i) Pandemic COVID-19; (ii) learning model; and (iii) online learning—analysis technique using content analysis. The results showed four appropriate learning models used in the online learning process: ICT -based learning models, problem-based learning models, blended learning models, and module-based learning models. The four learning models can support a distance learning system, increase student independence, improve digitalization skills and discipline, and increase student collaboration.